Inflammatory Bowel Disease: Predictors and Causes of Early and Late Hospital Readmissions. Issue 10 (October 2017) - Mudireddy, Prashant; Scott, Frank; Feathers, Alexandra; Lichtenstein, Gary R.
Abstract : Background and Aims: The rate of hospital readmission after discharge has been studied extensively in chronic conditions such as hepatic cirrhosis, diabetes mellitus, chronic obstructive pulmonary disease, and heart failure. Causative factors associated with hospital readmission have not been adequately investigated in patients with inflammatory bowel disease (IBD). We studied the rate, causes, and factors that predict readmissions at 1 month, 3 months, and 1 year in patients with IBD. Methods: We performed a retrospective cohort study using the electronic medical record of a tertiary academic medical center, encompassing 3 large hospitals to identify patients discharged between January 2007 and December 2010 with a primary discharge diagnosis of either ulcerative colitis or Crohn's disease. The index admission was defined as the first unplanned admission during this period. Readmission was defined as unplanned admission (because of any cause) occurring within 1 week, 1 month, 3 months, and 1 year from the index admission. To identify factors predictive of readmissions, we compared social, demographic, and clinical features at the index admission of patients with readmission and those with no readmissions. Multivariate logistic regression analyses were performed to identify variables associated with 1-month, 3-month, and 1-year readmissions. Results: A total of 439 index admissions with a primary discharge diagnosis of either ulcerative colitis or Crohn's disease were eligible for inclusion in the study. These patients accounted for a total of 785 admissions to the health system during the study period. The unplanned readmission rates were 5% at 1 week, 14% at 1 month, 23.7% at 3 months, and 39.2% at 1 year. The most common reasons for readmissions were IBD exacerbations, infections, and abdominal pain. On multivariate analysis, receiving total parenteral nutrition (odds ratio [OR] = 2.3; 95% confidence interval [CI], 1.22–4.30) and intensive care unit stay during index admission (OR = 3.61; 95% CI, 1.38–9.46) predicted both early and late readmissions, whereas sex, race, insurer, and outside hospital transfers predicted 1-year readmission. Receiving steroids (OR = 0.52; 95% CI, 0.23–1.15) at index admission was protective against 1-month readmission; being discharged on biologics (OR = 0.44; 95% CI, 0.19–1.02) was protective against 3-month readmission. Conclusions: Both early and late hospital readmissions are common in patients with IBD. Because frequent readmissions are indicators of poor quality of care, future prospective studies using larger cohorts of patients are needed to identify modifiable factors in patient care before discharge to improve quality of care, prevent readmissions, and consequently reduce health care costs. Abstract : Article first published online 29 August 2017.